Minimal warm inflation with complete medium response. Issue 6 (15th June 2021) - Laine, M.; Procacci, S.
Abstract: If a homogeneous field evolves within a medium, with the latter gradually picking up a temperature, then the friction felt by the field depends on how its evolution rate compares with medium time scales. We suggest a framework which permits to incorporate the contributions from all medium time scales. As an example, we illustrate how warm axion inflation can be described by inputting the retarded pseudoscalar correlator of a thermal Yang-Mills plasma. Adopting a semi-realistic model for the latter, and starting the evolution at almost vanishing temperature, we show how the system heats up and then enters the "weak" or "strong" regime of warm inflation. Previous approximate treatments are scrutinized.